1995
DOI: 10.1289/ehp.95103s935
|View full text |Cite
|
Sign up to set email alerts
|

Immunotoxicity of PCBs (Aroclors) in relation to Great Lakes.

Abstract: Polychlorinated biphenyls (PCBs) are among the most widespread environmental pollutants and a prominent contaminant of the Great Lakes basin. Due to their resistance to biodegradation and lipophilic properties, PCBs bioaccumulate in fish tissues and in fish-eating humans. PCBs are also known to cross the placenta and to be excreted into the mother's milk, thus predisposing the infant to potentially adverse health effects. For example, a higher incidence of bacterial infections was reported for breast-fed infan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 88 publications
0
14
0
Order By: Relevance
“…Not surprisingly, as it is not clearly established to be a risk factor for small size at birth, confounding by mercury also did not explain the associations observed, although seafood is an important source of this contaminant 59. Further study is needed to elucidate whether these relationships observed are causal and to identify the mechanisms involved, which might be related to other contaminants or contaminant mixtures 26 58…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Not surprisingly, as it is not clearly established to be a risk factor for small size at birth, confounding by mercury also did not explain the associations observed, although seafood is an important source of this contaminant 59. Further study is needed to elucidate whether these relationships observed are causal and to identify the mechanisms involved, which might be related to other contaminants or contaminant mixtures 26 58…”
Section: Discussionmentioning
confidence: 90%
“…It has been suggested that adverse effects on fetal growth might be attributable in part to organic pollutants such as PCBs, for which relatively high levels have been reported for some types of seafood, including tuna, in Spain 21 55 56. Mechanisms linking such pollutants to fetal growth are not established27 but may involve effects on endocrine,23 28 thyroid57 or immune function 58. However, associations with SGA remained similar after adjusting for serum levels of several pollutants, suggesting that associations between may be more complex than a simple increase in the burden of these compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The developing immune system appears to be highly sensitive to toxic effects, and experimental animal studies and in vitro assays have shown immunomodulatory effects of persistent organic pollutants (POPs), especially polychlorinated biphenyls (PCBs) [2-5], organochlorine pesticides (OCPs) [5-7], and perfluoroalkyl substances (PFASs) [8-10], as well as mercury and other metal compounds [11, 12]. These immunotoxicants are ubiquitous, most are persistent, and they are widely detected in children and adults from the general population [13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in addition to the described human health studies of children, other researchers have demonstrated in laboratory animal studies a number of comparable developmental and behavioral effects reported in children (e.g., Rice, 1997;Arnold et al, 1995;Tryphonas, 1995).…”
Section: S6mentioning
confidence: 87%